Changes in the number and characteristics of tertiary hospital psychiatric admissions in south Croatia before and during the COVID-19 pandemic: a retrospective study - Tea Vukićević; Tonka Borovina Marasović; Andrea Botica; Tonći Mastelić; Toni Utrobičić; Trpimir Glavina; Livia Puljak; Svjetlana Došenović (BMC Psychiatry)
Abstract Background There is mixed evidence on the impact of the Coronavirus disease (COVID-19) pandemic on psychiatric hospital care for people with severe mental diseases, possibly due to regional differences. There is a significant gap in knowledge regarding the specific impact of the COVID-19 pandemic on mental health in Croatia, a country in South-Eastern Europe. Our study aimed to evaluate the number and characteristics of psychiatric hospitalizations in the year before and during the first year of the COVID-19 pandemic in a tertiary hospital in south Croatia. Methods This was a retrospective study of adult psychiatric hospitalizations at the University Hospital of Split, Croatia. Sociodemographic and clinical data of inpatients during the first year of the COVID-19 outbreak (March 1, 2020 – March 1, 2021) and the year before the pandemic (March 1, 2019 - February 29, 2020) were compared. Incidence rate ratio (IRR) was used to compare the number of hospitalizations; while sociodemographic and hospitalization characteristics were compared between the two periods with the Mann-Whitney U test or chi-squared test, as appropriate. Results A significant reduction in hospitalization rate was observed during the COVID-19 pandemic (IRR = 0.72, 95% confidence interval 0.67–0.78, P < 0.0001). Compared to the year before the pandemic, hospitalizations due to suicidality increased almost 3 times, while hospitalizations due to both autoagression and heteroagression increased almost 4 times (P = 0.000). The proportion of hospitalized patients diagnosed with schizophrenia, schizotypal, and delusional disorders was significantly higher during the pandemic (61% vs. 52%), while neurotic, stress-related, and somatoform disorders decreased significantly (5.9% vs. 10%, P = 0.001). Furthermore, inpatients during the COVID-19 year were younger (P = 0.004), more educated (P = 0.040), had a higher prevalence of personal history of psychiatric diseases (P = 0.024), and experienced longer hospital stays (P = 0.002). Conclusions The COVID-19 pandemic caused a significant reduction in the psychiatric hospitalization rate at a tertiary university hospital in Croatia, with an increase in patients presenting with suicidality, aggression, and severe mental illnesses such as schizophrenia, schizotypal, and delusional disorders. These findings could help healthcare systems better adapt to the needs of the most vulnerable patients and address challenges in maintaining continuity of psychiatric care during public health crises.